Varied spectrum of lupus erythematosus: case series - P., Adithyan; S., Revathy (International Journal of Research in Dermatology, 2023)
Autoimmune connective tissue disorders represent polygenic clinical disorders that have heterogenous and overlapping clinical features. Lupus erythematosus (LE) is a connective tissue disorder that affects multiple organ systems with increased incidence among female population compared to males (9:1 F:M ratio). Skin is 2nd most frequent organ to be affected in LE after joints. Cutaneous lesions are a source of disability and on many occasions, an indicator of internal disease and these lesions may be specific to lupus/seen in other conditions as well. Correlation between clinical, histopathology, immunofluorescence, and serologic profiles (Anti-nuclear antibody) remains crucial as no single clinical feature or lab abnormality can confirm the diagnosis of LE. Treatment consists of sun protection, topical sunscreens, systemic steroids, antimalarials, immunosuppressives and biologicals. Effective treatment should be initiated at the earliest to prevent complications. Herein we report 4 cases of LE with varied presentation.